Effects of “Longitudinal Gastrojejunostomy” on Malabsorption in a Rat Model of Short Bowel Syndrome - Sinan Arıcı; Osman Bilgin Gülçiçek; Aytaç Biricik; Erkan Yavuz; Hakan Yiğitbaş; Candaş Erçetin; Aslı Kahraman Akkalp; Atilla Çelik (Bagcilar Medical Bulletin, 2023)

(untitled)
Objective:Short bowel syndrome (SBS) is a serious and chronic disorder of inadequate absorption of nutrients and fluid from the intestines. The most significant symptom of SBS is malnutrition. Weight loss due to malnutrition raised the morbidity and mortality rates of patients to a disappointing level. The use of making longitudinal gastrojejunostomy is a technique to grow neomucosa or intestinal metaplasia in the gastric mucosal surface and increase the intestinal transit time.Method:Three groups (Sham, SBS, longitudinal gastrojejunostomy) were created for 24 Wistar-Hannover rats. The 1st group was determined as the Sham group. SBS was induced in animals in group 2 with appropriate intestinal resection. Longitudinal gastrojejunostomy was additionally performed in rats with SBS in group 3. At the end of the 14th day all rats were weighted, euthanized, and blood sample was collected and anastomotic parts were resected for histopathological examination.Results:Weight loss was significantly less in group 3 and vitamin B12 and GLP-2 levels were significantly higher in group 3 compared to group 2. Longitudinal antiperistaltic gastrojejunostomy promotes intestinal metaplasia in the gastric mucosa and increased the absorption surface.Conclusion:This surgical procedure can be used to increase the absorption surface area in SBS. However, this needs to be supported by sufficiently robust clinical trials.